Financial Distress Perbankan di Indonesia: Studi Komparasi Krisis Global 2008 dan Krisis Pandemi COVID-19 - Ema Safutri Dahari; Herlina Pusparini; Isnawati (Distribusi - Journal of Management and Business, 2023)
This study aims to find the impact that arose due to the 2008 global crisis and the COVID-19 pandemic crisis on banking financial distress by using the grover model as a proxy in seeing the value of financial distress. The research method used in this research is quantitative. The results of the research that emerged were that based on SPSS 25, in testing before and during the 2008 global crisis the significance value that appeared was 0.082 which indicated that there was no difference that appeared before and during the crisis. However, in the COVID-19 pandemic crisis, the significance value that appears is 0.000, which indicates that there are differences before and during the crisis. When viewed through the results of financial distress data, the percentage level of the number of companies experiencing financial distress from before and during the crisis has increased. Therefore, it can be said that the crisis indirectly affects the financial distress of banks.